Penerapan Asas Keadilan Dalam Penetapan Nomor Urut Partai Politik Peserta Pemilihan Umum Tahun 2024 - Aji, Alan Bayu (Jurnal Hukum In Concreto, 2023)
The rules regarding the 2024 General Election provide different treatment between parties participating in the general election that have already passed in 2019 and political parties participating in the general election that are new or have not yet passed the 2024 general election. This form of inequality is shown through the determination of serial numbers of political parties , where those who have passed the 2019 general election can use the old serial number or draw it again, while the new political parties must draw their serial number. This research has a focus on studying how to apply the principle of justice in determining the serial number of participants in the 2024 general election and how the concept of applying the principle of justice in the future will apply to the principle of justice. This research is a normative legal research with a doctrinal approach that is processed conceptually. The results of this study indicate that the application of the principle of justice does not occur in the process of determining the serial number of parties participating in the 2024 election, so an evaluation of the rule of law is needed in order to ensure that the principle of justice can be carried out properly.